Long‐term inhibition of miR‐21 leads to reduction of obesity in db/db mice. (20th August 2014) - Seeger, Timon; Fischer, Ariane; Muhly‐Reinholz, Marion; Zeiher, Andreas M.; Dimmeler, Stefanie
<x xml:space="preserve">Abstract</x> Objective To assess the effect of long‐term pharmacological inhibition of miR‐21 in a model of metabolic syndrome and obesity. Methods Aged db/db mice were treated with locked nucleic acid‐modified anti‐miRs directed against miR‐21 (LNA‐21), control LNAs or PBS for 18 weeks. Cardiac function was assessed by echocardiography and the effect on body weight and white adipose tissue (WAT) was evaluated. Results MiR‐21 expression was efficiently inhibited in the heart and WAT with no apparent liver toxicity or deterioration of kidney function. MiR‐21 inhibition had no effect on cardiac hypertrophy as well as systolic and diastolic cardiac functions. However, levels of cardiac collagen 1 were modestly reduced in LNA‐21 treated mice. MiR‐21 inhibition reduced body weight, as well as adipocyte size and serum triglycerides were significantly decreased. The miR‐21 targets TGFβ‐receptor 2 (TGFBR2) and phosphatase and tensin homolog (PTEN) were derepressed in WAT of LNA‐21 treated mice and Sprouty1 and 2 were increased after miR‐21 inhibition. Conclusions Long‐term treatment with LNA‐21 is safe and efficiently suppresses miR‐21 expression. Cardiac function was not affected. LNA‐21 treatment led to a significant weight loss and reduces adipocyte size as well as derepression of the targets TGFRB2, PTEN, and Sprouty1 and 2.